Design of a Community-Based Adaptive Drainage System for Coastal Flood Mitigation: A Case Study of Kampung Tanah Baru, Bekasi Regency - Salim, Indra Putra; Hadiprono, Saputro; Risa, Kusmiatun Andar; Huri, Daman (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2025)
This study investigates the lived experiences of coastal communities in addressing the impacts of tidal flooding and pluvial inundation arising from the absence of drainage infrastructure in Kampung Tanah Baru, Hurip Jaya Village, Babelan District, Bekasi Regency. Utilizing a phenomenological approach within the Community-Based Environmental Management (CBEM) theoretical framework, the study examines residents' environmental perceptions, collective social responses, and the ecological implications of recurrent flooding. Primary data were obtained through in-depth interviews, participatory observations, and document analysis. The results reveal that inadequate drainage leads to persistent waterlogging and environmental degradation and significantly hinders local socio-economic functions. These empirical findings provide a critical foundation for formulating an adaptive and sustainable community-based eco-drainage system tailored to the unique socio-environmental context of coastal settlements.